2012
DOI: 10.4161/cc.21669
|View full text |Cite
|
Sign up to set email alerts
|

The RelB subunit of NFκB acts as a negative regulator of circadian gene expression

Abstract: The circadian system controls a large array of physiological and metabolic functions. The molecular organization of the circadian clock is complex, involving various elements organized in feedback regulatory loops. Here we demonstrate that the RelB subunit of NFκB acts as a repressor of circadian transcription. RelB physically interacts with the circadian activator BMAL1 in the presence of CLOCK to repress circadian gene expression at the promoter of the clock-controlled gene Dbp. The repression is independent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
48
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 50 publications
(44 reference statements)
5
48
0
1
Order By: Relevance
“…In our experiments, rhythmicity of circadian and metabolic genes is suppressed or attenuated at the site of infection, supporting the concept of intimate bidirectional communication between the circadian and immune systems (36,37). Our hypothesis is that immune factors contribute to the daily coordination of the circadian system, but powerful immunological challenges send signals to disrupt this regulation, possibly by uncoupling some of the circadian outputs, leading to reduction of the amplitude of the oscillations.…”
Section: Discussionsupporting
confidence: 81%
“…In our experiments, rhythmicity of circadian and metabolic genes is suppressed or attenuated at the site of infection, supporting the concept of intimate bidirectional communication between the circadian and immune systems (36,37). Our hypothesis is that immune factors contribute to the daily coordination of the circadian system, but powerful immunological challenges send signals to disrupt this regulation, possibly by uncoupling some of the circadian outputs, leading to reduction of the amplitude of the oscillations.…”
Section: Discussionsupporting
confidence: 81%
“…CLOCK complexes with p65 causing increased acetylation and phosphorylation of p65 and enhancing the activity of the NF-B complex [115]. Both CLOCK mutant MEFs [116] and bone marrow derived macrophages (BMDMs) lacking CLOCK, are less responsive to LPS, and TNF␣ induced NF-B activation [65]. Therefore CLOCK may drive, whereas BMAL1 may limit, pro-inflammatory responses in macrophages.…”
Section: Clockmentioning
confidence: 99%
“…[66,116] Clock 19 Global • Obese and display impaired glucose sensitivity with insulin resistance and reduced islet size [112,113] • Increased plasma triglyceride and glucose levels [85,114] • Increased fibrotic damage in model of pulmonary fibrosis [87] • Impaired anti-oxidant defense [87] Cry1/Cry2 Global • Increased NAD+ and ATP. Decreased lactate and triglycerides in MEFs [95] • Greater inflammatory damage in CIA model [146] • Increased Cxcl1.…”
Section: Bmal1-a Master Regulatormentioning
confidence: 99%
“…Petrzilka and colleagues extended this work and showed that TNF-α requires p38 mitogenactivated protein kinases (MAPK) and/or calcium signalling to upregulate expression of several core clock genes but it can downregulate Dbp (clock controlled gene) expression independently from p38 but requires calcium signalling (Petrzilka et al 2009). And Bellet and co-workers showed that the RelB subunit of NF-kB interacts with BMAL1 protein and represses the circadian expression of Dbp (Bellet et al 2012). Overall, these studies provide clues to understand the cross-talk between the circadian and immune systems in inflammatory diseases.…”
Section: There Is a Circadian Variation In Immune Functionmentioning
confidence: 97%